Hanna Meretoja. The Narrative Turn in Fiction and Theory: The Crisis and Return of Storytelling from Robbe-Grillet to Tournier. Palgrave Studies in Modern European Literature. New York: Palgrave Macmillan, 2014. xviii + 282 pp. - Charles R. Sullivan (Studies in 20th & 21st Century Literature, 2017)
Review of Hanna Meretoja. The Narrative Turn in Fiction and Theory: The Crisis and Return of Storytelling from Robbe-Grillet to Tournier. New York: Palgrave Macmillan, 2014. xviii + 282 pp.
Keywords: Narrative; Robbe-Grillet; Tournier